Dengue vector control in Malaysia: a review for current and alternative strategies - Song, Quan-Ong (Penerbit Universiti Kebangsaan Malaysia, 2016)
Dengue is a major issue in Malaysia as the dramatic emerge of infection. Yet an effective vaccine or medicine is not yet available, although many attempts are undergoing. Dengue vector control is still considered the most effective way for controlling and preventing the transmission of dengue virus. Nonetheless, as the conventional approaches are less successful in managing the dengue transmission, it is time to review the current applied and other available approaches. Current dengue vector relied greatly on the chemical approach as space treatment either thermal or ULV fogging, however, the approach seem like under the expectation. Beside space treatment, new control methods for example biological control (bacterium Bacillus thuringiensis, predatory mosquito Toxorhynchites) and attractive trap were carried out at certain location of Malaysia. Moreover, new emerged approaches such as mass release of genetic modification or artificially Wolbachia infected male dengue vector for the objective of generating sterile offspring when mate with wild population is urge to be tested in Malaysia, although concerns have to be taken before the actual mass release. In conclusion, control of dengue vector shall not consist exclusively for a single approach, neither genetic modification of artificially Wolbachia infected technique, nor the conventional insecticidal treatment. It should, however, comprise of the environment management as the fundamental approach, a well-planned integrated control program and a good cooperation among the organization.